Assessing Local and Branch-specific Activity in Dendrites. (1st May 2022) - Moore, Jason J.; Robert, Vincent; Rashid, Shannon K.; Basu, Jayeeta
Highlights: Dendrites nonlinearly integrate inputs to increase neural complexity. Branch-specific dendritic activity shapes selectivity, plasticity, and behavior. Biophysics, spatiotemporal patterning, and inhibition structure dendritic activity. Blind patch clamp electrophysiology facilitates intracellular dendritic access. In vivo two-photon calcium imaging enables population dendritic imaging. Abstract: Dendrites are elaborate neural processes which integrate inputs from various sources in space and time. While decades of work have suggested an independent role for dendrites in driving nonlinear computations for the cell, only recently have technological advances enabled us to capture the variety of activity in dendrites and their coupling dynamics with the soma. Under certain circumstances, activity generated in a given dendritic branch remains isolated, such that the soma or even sister dendrites are not privy to these localized signals. Such branch-specific activity could radically increase the capacity and flexibility of coding for the cell as a whole. Here, we discuss these forms of localized and branch-specific activity, their functional relevance in plasticity and behavior, and their supporting biophysical and circuit-level mechanisms. We conclude by showcasing electrical and optical approaches in hippocampal area CA3, using original experimental data to discuss experimental and analytical methodology and key considerations to take when investigating the functional relevance of independent dendritic activity.